Late Tertiary and Early Pleistocene Paleosols in Northwestern Canada - Tarnocai, C.; Schweger, C.E. (ARCTIC, 1991)
Late Tertiary paleosols occurring in the unglaciated portion of the Yukon Territory of northwestern Canada have either Podzolic or Luvisolic soil development. The early Pleistocene paleosols in this area also display Luvisolic soil development in addition to cryogenic soil properties resulting from frost action. Most of these latter paleosols have deeply weathered sola and they usually have rubified argillic horizons. These soil properties suggest that the climate during the late Tertiary and early Pleistocene was warmer than at present. The cryogenic soil properties found in the early Pleistocene paleosols suggest that these soils were exposed to cold climates during subsequent glacial periods.Key words: paleosols, late Tertiary, early Pleistocene, northwestern Canada, soil environments, soil development Mots clés: paléosols, Tertiaire tardif, Pléistocène précoce, nord-ouest canadien, environnements pédologiques, formation des sols